A Balanced and Broad Approach to Technological Innovations - Quinet, Félix (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
Collective bargaining is a process on which technological change might not only have an impact but a process that should be strengthened through its responses to technological change.